STRATEGIC-BASED REGIONAL DEVELOPMENT IN BORDER AREA FOR NATIONAL DEFENSE - Sulistiani, Anisa; Mutaal, Muhammad Rofi'ud (Jurnal Ilmu Pemerintahan Widya Praja, 2024)
This research aims to analyze strategic-based development in the Natuna Regency area as Indonesia's gateway and its relevance in strengthening national security related to the South China Sea dispute dynamics. The North Natuna Sea, as part of the South China Sea, has significant marine resource potential and is a strategic shipping lane connecting the Pacific and Indian Oceans. However, the region is also caught up in complex territorial disputes involving countries such as China, Taiwan, Malaysia, the Philippines, Vietnam, and Brunei Darussalam. China's unilateral claim to the region, known as the nine-dashed line map, triggered rejection from neighboring countries, including Indonesia. This research uses a descriptive qualitative method with secondary data and utilizes various sources of scientific publications and national regulations. Data were analyzed using the Strategic-Based Regional Development (SBRD) approach, integrating social, economic, and institutional dimensions. The results show that the regional development of Natuna Regency through strengthening the infrastructure, fisheries, and fisheries' industrialization sectors is crucial in maintaining Indonesia's national stability and security, especially in the face of China's unilateral claims. While Indonesia has strengthened its military posture and diplomacy in the region, the lack of synergy between central and local governments and challenges in governance cause vulnerabilities that must be addressed. This study recommends more integrated planning between central and regional governments to strengthen local trust in national sovereignty. Keywords: Border Security; National Defense; Natuna; Regional Development; South China Sea.